ANALISIS PEMINJAMAN REKAM MEDIS GUNA MENUNJANG EFEKTIVITAS PELAYANAN RAWAT JALAN DI RUMAH SAKIT UMUM PINDAD BANDUNG - Meira Hidayati (POLITEKNIK PIKSI GANESHA, 2020)
This study aims to determine the analysis proses of borrowing medical records to support the effectiveness of outpatient services at Rumah Sakit Umum Pindad Bandung.The method used of qualitative research with descriptive approach. Data collection techniques used observation, interview and equipped with a literate review which has closely relevant to the subject matter. The suggestion gave to solve the problem: (1) borrow time is not up to standard, (2) many procedures in the process of borrowing medical records, so that borrowing time is not effective, (3) medical records that have been misplaced or not found in their place. As for the suggestion were given to the hospital including: (1) must determine the time limit for borrowing, (2) hospital need to resive the flow and procedures for borrowing medical records, (3) conduct a review for the need for medical record workforce.